Goethe's path to creativity: a psycho-biography of the eminent politician, scientist and poet - Holm-Hadulla, Rainer M. (Routledge, Taylor & Francis Group, 2019)
Zusammenfassung: "Goethe's Path to Creativity provides a comprehensive psycho-biography of Johann W. V. Goethe, a giant of modern German and European literary, political and scientific history. The book brings this influential work by Rainer Matthias Holm-Hadulla to the English language for the first time, in a newly elaborated edition. Goethe's path to creativity was difficult and beset by a multitude of crises, beginning with his birth, which was so difficult that he was initially not thought to have survived it, and ending with an infatuation that left him, at the age of 74, toying with the same kind of suicidal thoughts he had entertained as a twenty-year-old. Throughout his long life, he suffered bitter disappointments and was subject to severe mood swings. Despite being a gifted child, a widely recognised poet, and an influential scientist and politician, he spent his entire life loving and suffering; nonetheless, he had the exceptional ability to endure emotional pain and to transform his sufferings creatively. The way in which he mined his passions for creative impulses continues to inspire modern readers. Readers can apply the lessons they have learned from his life and use his strategies for their own creative art of living. Goethe's Path to Creativity will be of great interest to all engaged in the fields of creativity, literature, psychoanalysis, psychology, psychotherapy and personal growth."--Provided by publisher